2019
DOI: 10.12681/mms.19054
|View full text |Cite
|
Sign up to set email alerts
|

Visual observations of floating macro litter around Italy (Mediterranean Sea)

Abstract: We report the results of a visual survey of floating natural (NML) and anthropogenic (AML) macro-litter (>2.5 cm) performed in the central part of the Mediterranean Sea during a dual-use campaign onboard the Italian Navy tall ship “Amerigo Vespucci” which circumnavigated the Italian peninsula during May-June 2016. The distribution, abundance and composition of floating marine litter were assessed using a 10 m fixed-width strip transect method. Over 88 h of transect counts were performed, for a total of 168 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…The reported data showed that there was a fairly large range of values (from 22 to 1934 g/km 2 ), but noted that the area of the north-western Tyrrhenian Sea presented the greatest abundance. The latest studies that have focused on the floating ML in the Mediterranean, and in particular, in the waters surrounding the Italian peninsula, confirmed this [54,61,74]. The coasts included in these marine areas within the Pelagos Sanctuary are of extreme environmental importance, as they are rich in parks and MPAs located both near urban areas and in places that are not easily accessible and far from sources of direct pollution.…”
Section: Introductionmentioning
confidence: 81%
“…The reported data showed that there was a fairly large range of values (from 22 to 1934 g/km 2 ), but noted that the area of the north-western Tyrrhenian Sea presented the greatest abundance. The latest studies that have focused on the floating ML in the Mediterranean, and in particular, in the waters surrounding the Italian peninsula, confirmed this [54,61,74]. The coasts included in these marine areas within the Pelagos Sanctuary are of extreme environmental importance, as they are rich in parks and MPAs located both near urban areas and in places that are not easily accessible and far from sources of direct pollution.…”
Section: Introductionmentioning
confidence: 81%
“…1 A-C). Floating plastic debris is common off Madeira (Chambault et al 2018) and Giglio (Campanale et al 2019). However, while Madeira is an isolated off-shore island exposed to open Atlantic waves, Giglio is a nearshore island that is relatively wave-sheltered among larger nearby islands (Elba, Corsica and Sardinia) and the Italian mainland.…”
Section: Discussionmentioning
confidence: 99%
“…To date, most studies on marine plastic pollution examined pelagic environments (e.g. Chambault et al 2018, Campanale et al 2019. In contrast, there has been surprisingly little research on plastic debris in rocky intertidal habitats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to consider novel plastic debris types in marine conservation policy it is necessary to investigate whether 'plasticrusts' and 'pyroplastics' occur on other coasts as well. Since plastic pollution in the Tyrrhenian Sea (European Mediterranean) is relatively high (Campanale et al 2019), we examined for the first time the occurrence of 'plasticrusts' and 'pyroplastics' on Tyrrhenian Sea coasts.…”
Section: Introductionmentioning
confidence: 99%